Effect of Fly Ash on the Compressive Strength of Green Concrete - Chandio, S. A.; Memon, B. A.; Oad, M.; Chandio, F. A.; Memon, M. U. (Engineering, Technology & Applied Science Research, 2020)
This research paper aims at investigating the effects of fly ash as cement replacement in green concrete made with partial replacement of conventional coarse aggregates with coarse aggregates from demolishing waste. Green concrete developed with waste materials is an active area of research as it helps in reducing the waste management issues and protecting the environment. Six concrete mixes were prepared using 1:2:4 ratio and demolishing waste was used in equal proportion with conventional aggregates, whereas fly ash was used from 0%-10% with an increment of 2.5%. The water-cement ratio used was equal to 0.5. Out of these mixes, one mix was prepared with all conventional aggregates and was used as the control, and one mix with 0% fly ash had only conventional and recycled aggregates. The slump test of all mixes was determined. A total of 18 cylinders of standard size were prepared and cured for 28 days. After curing the compressive strength of the specimens was evaluated under gradually increasing load until failure. It is observed that 5% replacement of cement with fly ash and 50% recycled aggregates gives better results. With this level of dosage of two waste materials, the reduction in compressive strength is about 11%.